Poverty and children's adjustment - Luthar, Suniya S. (Developmental clinical psychology and psychiatry, 1999)
Poverty and Children's Adjustment gives an interdisciplinary perspective on the effects of poverty, lack of education, and other negative socioeconomic forces on children's development. This volume provides an in-depth review of the literature on psychopathology among children faced with sociodemographic disadvantage, as well as suggested directions for future research. Suniya S.